INDICATORS AND DIGITAL MONITORING SYSTEM FOR ASSESSING THE EFFECTIVENESS OF SPIRITUAL AND EDUCATIONAL ACTIVITIES IN HIGHER EDUCATION INSTITUTIONS (Web of Teachers: Inderscience Research, 2026)
The article presents the scientific foundations of the system of indicators and digital monitoring mechanisms for assessing the effectiveness of spiritual and educational activities in the higher education system of Uzbekistan. Effective mechanisms are proposed for determining the spiritual and moral development of students and teachers through the use of digital technologies, gamification, psychodiagnostic tests, and electronic portfolios.